Selective Patterned Growth of ZnO Nanoneedle Arrays - Mihailova, I.; Krasovska, M.; Sledevskis, E.; Gerbreders, V.; Mizers, V.; Bulanovs, A.; Ogurcovs, Andrejs (Sciendo, 2023)
Nanostructured coatings are widely used to improve the sensitivity of various types of sensors by increasing the active surface area compared to smooth films. However, for certain applications (in some cases), it may be necessary to achieve selectivity in the coating process to ensure that nanostructures only form in specific areas leaving interelectrode spaces free of nanostructures. This article discusses several methods for creating intricate ZnO nanostructured patterns, including area selective application of Zn acetate seeds followed by hydrothermal growth, selective thermal decomposition of zinc acetate via laser irradiation followed by hydrothermal growth, and the electrochemical deposition method. These methods enable ZnO nanostructures to grow onto designated surface areas with customised, patterned shapes, and they are rapid, cost-effective, and environmentally benign. The article examines the process of producing a nanostructured coating with a complex shape and discusses several factors that can impact the quality of the final product. These include the influence of the thermocapillary flows and the “coffee stain” effect on the deposition of a seed layer of zinc oxide from an ethanol solution of zinc acetate. Additionally, the study found that using a protective screen during the growth of nanostructures can reduce the occurrence of unintended parasitic structures in areas lacking a seed layer. Overall, the article presents various techniques and strategies to improve the quality of nanostructured coatings. We have proven that the use of laser radiation to create a seed layer does not impact the final morphology of the resulting nanostructures. However, when combined with computer-controlled technology, this approach allows for the creation of intricate patterns made up of micrometre-sized lines which cannot be achieved by using other methods. The article also demonstrates an electrochemical technique for obtaining zinc oxide nano-structures that can selectively coat metal electrodes without requiring a seed layer. --//--This is an open access article Mihailova, I., Krasovska, M., Sledevskis, E., Gerbreders, V., Mizers, V., Bulanovs, A. and Ogurcovs, A.. "Selective Patterned Growth of ZnO Nanoneedle Arrays" Latvian Journal of Physics and Technical Sciences, vol.60, no.6, 2023, pp.35-53. https://doi.org/10.2478/lpts-2023-0035 published under the CC BY-NC-ND 4.0 licence.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Hydrothermal synthesis; nanostructures; selective patterning; ZnO